GST IN INDIA: PROBLEMS AND PROSPECTS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The Goods and Services Tax (GST), implemented  in India on July 1, 2017, has been regarded as  the most significant milestone in the history  of taxation since Independence. The GST was  planned to be implemented in April 2010, but  was postponed due to political issues and conflict  of interests of the stakeholders. The main purpose  of the GST is to simplify the taxation system by  subsuming all sorts of indirect taxes like, Central  Excise, VAT, Sales Tax, and Service tax and  implement ‘one nation one tax’ system in India. The objective of the paper is to examine the  working of the GST and its prospects in India.  As GST has been recently implemented only  recently, the full impact of the system is still  awaited. The research is exploratory in nature,  and uses secondary sources of data, including  journals, newspapers, websites of various  relevant authorities, etc. The conclusion being  positive in tone suggest several ways through  which the GST can be reformed.
Keywords: taxation; milestone; exploratory; conclusion